FACTORS OF MOTIVATION OF ACADEMIC ACTIVITIES OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS (Psychology Travelogs, 2025)
The article provides a theoretical study of the issues of motivational support of the educational process in higher education institutions. Motivation is characterized as a multifactorial, dynamic formation that is formed under the influence of both internal personal factors and the socio-pedagogical context.It is proven that educational activity is polymotivated, since the student's activity has different sources. The types of sources of activity are analyzed: internal, external and individual.It is noted that the main characteristics of educational motivation include stability and dynamism. Dominant internal motives determine the stability of educational motivation, the hierarchy of its main substructures. Social motives determine the constant dynamics of incentives.The results of the study of the motivation of students' educational activity are presented. The structure, dynamics and change in the hierarchy of motives of students' educational activity in the learning process are revealed.
Keywords: student youth; motivational readiness; learning motivation; development of motivation for educational activity; factors of learning motivation; structure and hierarchy of motives of learning activity